SELF-EFFICACY, ACHIEVEMENT GOALS, AND ACHIEVEMENT: ACADEMIC HELP-SEEKING TENDENCIES AS MEDIATORS - Luo, Wenshu; Zhang, Yenming (PEOPLE: International Journal of Social Sciences, 2015)
This study investigated how students’ academic help-seeking tendencies mediate motivation and subsequent achievement. A large sample of Singapore Secondary 2 students took a survey on math self-efficacy, achievement goals (mastery and performance), and help-seeking tendencies (adaptive, expedient, and avoidant), followed by a math achievement test about 3 months later. We conducted structural equation modeling and found that after controlling for gender and previous math achievement, students’ help-seeking tendencies fully mediated the predictive relationship from math self-efficacy and achievement goals to subsequent math achievement. More specifically, math self-efficacy was associated positively with adaptive help seeking, mastery goals were associated positively with adaptive help seeking and negatively with avoidant help seeking, and performance goals were associated negatively with adaptive help seeking and positively with both expedient and avoidant help seeking. Adaptive help seeking in turn positively and expedient help seeking negatively predicted subsequent math achievement. Through the mediation of help-seeking tendencies, math self-efficacy and mastery goals positively and performance goals negatively predicted subsequent math achievement. The importance of help seeking in learning and implications for classroom teaching are discussed.